Cryptocaryon irritans Infections (Marine White Spot Disease) in Fish - Roy P. Yanong (EDIS)
FA164, a 10-page illustrated fact sheet by Roy P. E. Yanong, describes this significant disease problem for marine aquarists and commercial mariculture worldwide — signs of disease, biology and life cycle, immunity, diagnostics, prevention and control, disinfection, and biosecurity considerations. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, December 2009.